2015
DOI: 10.1021/jp508177k
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Growth on Pt(111) by Ethylene Chemical Vapor Deposition at Surface Temperatures near 1000 K

Abstract: The nucleation and growth of graphene islands on a Pt(111) surface were examined at temperatures near 1000 K. Graphene was grown by chemical vapor deposition of ethylene and a low-energy electron microscope (LEEM) was used to image the growing graphene islands with resolution of 10 nm and to perform spatially-localized electron diffraction. It is shown that graphene grows bi-directionally over the step edges of Pt and its formation can induce substantial changes in the platinum surface morphology. Average size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 79 publications
(227 reference statements)
3
32
0
Order By: Relevance
“…The results of rare-gas scattering from these graphenes are compared to that from HOPG, which serves as a reference for nearly freestanding graphene supported by the van der Waals interaction. Graphene on Pt(111) is known as the model of nearly freestanding graphene [14][15][16][17][18][19][20][21]. Density functional theory (DFT) calculations have shown that the graphene-substrate distance of gr/Pt(111) is approximately 3.3Å, which is nearly the same as the 3.354Å interlayer distance in HOPG [14,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The results of rare-gas scattering from these graphenes are compared to that from HOPG, which serves as a reference for nearly freestanding graphene supported by the van der Waals interaction. Graphene on Pt(111) is known as the model of nearly freestanding graphene [14][15][16][17][18][19][20][21]. Density functional theory (DFT) calculations have shown that the graphene-substrate distance of gr/Pt(111) is approximately 3.3Å, which is nearly the same as the 3.354Å interlayer distance in HOPG [14,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Choosing different catalysts is capable to change the reactivity, reduce the reaction barrier and meanwhile tune the reaction path and selectivity towards precursors. Up to now, many transition metal and noble metal catalysts have been used to promote the decomposition of carbon sources and the later nucleation and growth, including Ni [17,60], Cu [25,61], Fe [62,63], Co [64,65] and Pt [66,67]. In the initial stage, precursor molecules can be decomposed into carbon radicals on the surface of the catalyst, then diffuse over the surface of the catalyst or dissolve into the catalyst.…”
Section: Catalyst Design To Reduce the Energy Barrier Of The Reactionmentioning
confidence: 99%
“…As much as now, there are plentiful research articles are explaining graphene based inorganic nanocomposites for various types of catalyst activity. To illustrate, graphene nanocomposite with noble metals such as (Ag, Au, Pt, Pd) are employed as a catalyst for hydrogenation reaction and oxygen reduction reaction . Furthermore, metal oxide like MoS 2 , Co 3 O 4 , ZnO, Fe 3 O 4 , SiO 2 , and CoFe 2 O 4 are used as an effective photocatalyst in the photodegradation of organic pollutant and hydrogen evolution in water splitting …”
Section: Introductionmentioning
confidence: 99%